The Double Donut Schmidt Camera for the cosmogenic neutrino detection. Issue 3 (1st August 2020) - Mazzinghi, P.; Spillantini, P.
Abstract: This work discusses a variation of the Double Donut Schmidt Camera (DDSC), originally proposed for the EUSO-FF (EUSO on Free Flyer) project and devoted to the observation of UHECRs from space with a threshold of about 5 * 10 19 eV for a 600 km altitude. Increasing the entrance pupil area by a factor 3, and then lowering the energy threshold to about 8 EeV (assuming for the differential energy spectrum of UHECR's the index −2.7), the proposed system will allow the observation of some 'cosmogenic neutrino' events in the 10 18 –10 19 eV range, where most of their flux is expected. The scalability of the DDSC design and the high Technological Readiness Level (TRL5) reached in the last decade for ultra-light, deployable, active mirrors does not set conceptual limits on the possible diameter of the primary mirror. We then propose to scale up the optics until the UV light detector in the focal plane will fill the whole diameter of the fairing of the considered launcher (4.2 m diameter assumed as in EUSO-FF baseline for Ariane 5/6 class). This will make necessary to deploy the corrector plate in orbit, in order to accommodate it into the fairing. This technology is still to be evaluated, but as the plate has a small refractive power, its tolerances are much broader than those of the primary mirror and it should be technologically feasible. With this upgrade, EUSO-FF, in addition to detecting more UHECR events, could also act as a precursor of a UHE neutrino observatory from space, addressing the problems to be faced for its realization.